Transformation of chicken myelomonocytic cells by a retrovirus expressing the v-myb oncogene from the long terminal repeats of avian myeloblastosis virus but not Rous sarcoma virus. - Press, R D (1992)
To test the effect of long terminal repeat (LTR) regulatory sequences on the transforming capability of the v-myb oncogene from avian myeloblastosis virus (AMV), we have constructed replication-competent avian retroviral vectors with nearly identical structural genes that express v-myb from either AMV or Rous sarcoma virus (RSV) LTRs. After transfection into chicken embryo fibroblasts, virus-containing cell supernatants were used to infect chicken myelomonocytic target cells from preparations of 16-day-old embryonic spleen cells. Both wild-type AMV and the virus expressing v-myb from AMV LTRs (RCAMV-v-myb) were able to transform the splenocyte cultures into a population of immature myelomonocytic cells. The transformed cells expressed the p48v-Myb oncoprotein and formed compact foci when grown in soft agar. In contrast, the virus expressing v-myb from RSV LTRs (RCAS-v-myb) was repeatedly unable to transform the same splenocyte cells, despite being able to infect fibroblasts with high efficiency. This difference in the transforming activities of v-myb-expressing viruses with different LTRs most likely results from the presence of a factor (or factors) within the appropriate myelomonocytic target cell that promotes specific expression from the AMV but not from the RSV LTR.